SYNTHESIS, SPECTRAL CHARACTERIZATION, AND IN SILICO STUDIES OF N-MANNICH BASES OF NOVEL SUBSTITUTED BENZIMIDAZOLE DERIVATIVES AS ANALGESIC, ANTIFUNGAL, AND POTENT INHIBITORS FOR BREAST CANCER - BHAGYASHRI D JADHAV; SUSHIL P NARKHEDE (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The aim of the present study is to synthesize N-Mannich bases of novel series of substituted benzimidazole derivatives and their in silico simulation. Methods: This study presents research on the synthesis of N-Mannich bases of novel series of substituted benzimidazole derivatives using substituted benzimidazoles as the starting compound. In silico simulation and absorption, distribution, metabolism, and excretion prediction of all the compounds are demonstrated by their computational studies. Results: All synthesized compounds were analyzed using 1hydrogen nuclear magnetic resonance, Fourier transform infrared, and mass spectrometry to validate their structures. In silico simulation against the 1C14 as analgesic, 5fsa as antifungal, and 600 k as breast cancer protein database indicated that synthesized compounds have moderate-to-good-binding energy. Conclusion: Overall, the computational analyses indicate that the derivatives synthesized show encouraging pharmacokinetic characteristics and affinity, positioning them as potential candidates for further advancement as therapeutic agents.